429-2009-HW3key

# 429-2009-HW3key - Systems Bioengineering III: Homework 3...

This preview shows pages 1–4. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Systems Bioengineering III: Homework 3 Key Rahul Karnik October 5, 2009 1 Assuming the system has equilibrated, we know that at t = 0- both dx 1 dt and dx 2 dt are zero. Setting dx 1 dt = 0 in the first ODE: 0 = k 1 S- α 1 x 1 (0- ) x 1 (0- ) = k 1 S α 1 Similarly, setting dx 2 dt = 0 in the second ODE: 0 = k 2 x 1 (0- )- α 2 x 2 (0- ) x 2 (0- ) = k 2 x 1 (0- ) α 2 = k 1 k 2 S α 1 α 2 We can now use these values as initial conditions in the Laplace transform for modeling the system’s behavior after t = 0. 1 2 S ( t ) = S 1 cos( ωt- θ ) ˜ S ( s ) = Z ∞ S 1 cos( ωt- θ ) e- st dt = S 1 Z ∞ cos( ωt )cos( θ ) e- st dt + S 1 Z ∞ sin( ωt )sin( θ ) e- st dt = S 1 cos θ Z ∞ cos( ωt ) dt + S 1 sin θ Z ∞ sin( ωt ) dt = S 1 s cos θ s 2 + ω 2 + S 1 ωsinθ s 2 + ω 2 = S 1 ( s cos θ + ω sin θ ) s 2 + ω 2 We can use this expression for ˜ S ( s ) to find ˜ x 1 ( s ). ˜ x 1 ( s ) = 1 s + α 1 k 1 ˜ S ( s ) + k 1 S α 1 = 1 s + α 1 k 1 S 1 ( s cos θ + ω sin θ ) s 2 + ω 2 + k 1 S α 1 x 1 ( t ) = Z iω- iω e st 1 s + α 1 k 1 S 1 ( s cos θ + ω sin θ ) s 2 + ω 2 + k 1 S α 1 ds = k 1 S 1 cos θ- α 1 e- α 1 t α 2 1 + ω 2 + iωe iωt ( α 1 + iω )(2 iω ) +- iωe- iωt ( α 1- iω )(- 2 iω ) + k 1 S 1 ω e- α 1 t α 2 1 + ω 2 + e iωt ( α 1 + iω )(2 iω ) + e- iωt ( α 1- iω )(- 2 iω ) + k 1 S e- α 1 t α 1 (ignoring transient terms) = k 1 S 1 cos θ 2 e iωt α 1 + iω + e- iωt α 1- iω + k 1 S 1 sin θ 2 i e iωt α 1 + iω- e- iωt α 1- iω using r 1 = p ω 2 + α 2 , φ 1 = tan- 1 ω α 1 = k 1 S 1 cos θ 2 e iωt r 1 e iφ 1 + e- iωt r 1 e- iφ 1 + k 1 S 1 sin θ 2 i e iωt r 1 e iφ 1- e- iωt r 1 e- iφ 1 = k 1 S 1 cos θ r 1 e i ( ωt- φ 1 ) + e- i ( ωt- φ 1 ) 2 + k 1 S 1 sin θ r 1 e i ( ωt- φ 1 )- e- i ( ωt- φ 1 ) 2 i = k 1 S 1 r 1 [cos θ cos( ωt- φ 1 ) + sin θ sin( ωt- φ 1 )] = k 1 S 1 r 1 cos( ωt- θ- φ 1 ) = k 1 S 1 p ω 2 + α 2 1 ! cos( ωt- θ- tan- 1 ω α 1 ) So the theoretical values for gain and phase shift for x 1 are: 2 A x 1 = k 1 p ω 2 + α 2 1 φ x 1 = tan- 1 ω α 1 We can use the expression for ˜ x 1 ( s ) to find ˜ x 2 ( s ). ˜ x 2 ( s ) = 1 s + α 2 k 2 ˜ x 1 ( s ) + k 1 k 2 S α 1 α 2 = 1 s + α 2 1 s + α 1 k 1 k 2 S 1 ( s cos θ + ω sin θ ) s 2 + ω 2 + k 1 k 2 S α 1 + k 1 k 2 S α 1 α 2 Following a procedure very similar to that shown above for x 1 ( t ), we get: x 2 ( t ) = k 1 k 2 S 1 r 1 r 2 cos( ωt- θ- φ 1- φ 2 ) = k 1 k 2 S 1 p ω 2 + α 2 1 p ω 2 + α 2 2 !...
View Full Document

## This note was uploaded on 03/30/2010 for the course SBE 580.429 taught by Professor Joelbader during the Fall '09 term at Johns Hopkins.

### Page1 / 14

429-2009-HW3key - Systems Bioengineering III: Homework 3...

This preview shows document pages 1 - 4. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online